Argument Driven Inquiry Learning Integrated with Expressive Writing: to Enhance Students' Critical Thinking and Argumentation Skills - Saparianingsih, Ria; Darmawan, Nurani Hadnistia; Suparman, Silva Fadilah (Jurnal Ilmiah Profesi Pendidikan, 2025)
Learning in the twenty-first century demands that individuals, including future educators, be capable of meeting the challenges of globalization by developing their potential and various essential skills. Among these, critical thinking and argumentation are particularly important. One instructional approach that can foster these abilities is the Argument Driven Inquiry (ADI) model. This study seeks to enhance students’ critical thinking and argumentation abilities by integrating the ADI model with expressive writing. Employing a quasi-experimental design with a nonequivalent control group, the study involved 65 students from STKIP Bina Mutiara Sukabumi. The findings revealed that the integration of the ADI model with expressive writing significantly improved students’ critical thinking and argumentation abilities. The t-test result (0.00 < a = 0.05) confirmed the significant impact of this approach. Furthermore, the effectiveness test showed an average n-gain score of 0.69 for critical thinking and 0.60 for argumentation skills. Therefore, it can be inferred that integrating the ADI model with expressive writing effectively enhances students’ critical thinking and argumentation skills.